1996
DOI: 10.1016/0031-9422(95)00530-7
|View full text |Cite
|
Sign up to set email alerts
|

New aspects of anthocyanin complexation. Intramolecular copigmentation as a means for colour loss?

Abstract: Two series of structurally related anthocyanins, extracted from the blue flowers of Evolvulus pilosus cv. Blue Daze and from the blue-purple flowers of Eichhornia crassipes, exhibit remarkable colour stabilities in aqueous solution at mildly acidic pH values. All the pigments possess the same chromophore (delphinidin), but a different pattern of glycosylation and acylation. Moreover, one of the pigments has an apigenin 7-glucoside molecule (a flavone) attached to the glycosidic chain by two ester bonds with ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
56
0
2

Year Published

1996
1996
2024
2024

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 127 publications
(63 citation statements)
references
References 31 publications
5
56
0
2
Order By: Relevance
“…It has been reported as a general characteristic that an increase in the number of substitutions is accompanied by an increase in the molar absorptivity of the flavylium cation form when compared to their parent mono-and diglucosides (Figueiredo et al, 1996b). Our results showed a general hyperchromic effect of acylation of pg derivatives as compared to the parent pg-3-soph-5-glu, in particular, when 2 acylating groups were present.…”
Section: Resultssupporting
confidence: 36%
“…It has been reported as a general characteristic that an increase in the number of substitutions is accompanied by an increase in the molar absorptivity of the flavylium cation form when compared to their parent mono-and diglucosides (Figueiredo et al, 1996b). Our results showed a general hyperchromic effect of acylation of pg derivatives as compared to the parent pg-3-soph-5-glu, in particular, when 2 acylating groups were present.…”
Section: Resultssupporting
confidence: 36%
“…407 Dyrby et al 408 investigated acylated anthocyanins from red cabbage that have shown low sensitivity to photo-degradation in the 3-7 pH range and thermal stability, with respect to other non-acylated anthocyanins obtained from red grape, 409 black currant 410 and elderberry. 401,402,413,414 Molecular co-pigmentation between anthocyanin and other compounds (co-pigments) is an important stabilizing mechanism of chromophores. 408 In the past years, many of the aforementioned vegetables and many others were identified as potential natural source of stable anthocyanins.…”
Section: Anthocyaninsmentioning
confidence: 99%
“…lishizhenii was the lowest. The copigment indices (Cl) varied among species (Robinson and Robinson 1931, Asen et al 1972, Figueiredo et a/. 1996, Wang et a/.…”
Section: Flavone and Flavonol Composition Of Petalsmentioning
confidence: 99%